Role of Cone-Beam Computed Tomography in Assessment of Lateral Wall Thickness of Maxillary Sinus in Posterior Edentulous Maxilla - Debanti Giri; F. Lalrawngbawli; Tapan K. Giri; Debabrata Biswas; Saurav Banerjee; Tridib N. Banerjee (Journal of Pharmacy and Bioallied Sciences)
Objective: To use Cone Beam Computed Tomography (CBCT) to evaluate the lateral wall thickness (LWT) of the maxillary sinus in the posterior edentulous maxilla, as well as the effect of ridge height (RH), edentulous region, type of edentulism (Complete and partial), age, and gender, for the placement of dental implants. Materials and Methods: To conduct this cross-sectional study, A CBCT scan of 60 patients of different age groups was taken for analysis. Each parameter was evaluated at the edentulous sites in the premolar and molar regions due to missing one or more posterior teeth at four levels from sinus floor 3, 7, 10, and 15 mm with residual RH less than 10 mm. Data were analyzed using Friedman’s ANOVA and one-way ANOVA. Bootstrapped linear regression was performed to assess the influence of various variables on LWT. Results: LWT increased from 3 mm to 15 mm in all teeth except the first premolar region, with significant differences (P < 0.01). LWT was generally lower in premolars and higher in molars. Age, gender, and RH did not predict LWT (P > 0.05), However, the type of edentulism significantly predicted LWT. (P = 0.005). Conclusion: CBCT scans are recommended before sinus surgeries due to anatomical variations.